Miti in resnice o detoksifikaciji jeter z zdravilnimi rastlinami in prehranskimi dopolnili - Kreft, Samo (Farmacevtski vestnik, 2017)
Detoxification of liver is very tempting promise used to advertise many products, particularly food supplements containing medicinal plants. Legislation on health claims in European Union is still in transitional period and enables the use of some health claims that are not scientifically well established. Exploring the effects of detoxification is not easy, because the effect is not well-defined. It is also unclear who the target population is. The European Food Safety Authority received from the Member States proposals for 26 ingredients (especially medicinal plants) for the approval of health claims in relation to the detoxification of the liver, but none was yet approved. Most research was conducted with milk thistle, but according to the assessment by the European Medicines Agency (EMA) it is not sufficient. The monograph on milk thistle that will be published shortly, will probably not include any indications concerning the protection of the liver or detoxification.
Keywords: detoksifikacija jeter; pegasti badelj; Prehranski dodatki; varnost hrane; zdravila rastlinskega izvora